As contradições do Estado avaliador: experiências do ensino superior brasileiro - Biffi, Evandro José (2010)
This work has as study object the evaluation processes for higher education practiced in Brazil, and it tries to investigate if they have produced some improvement in IES and in degree courses. We consider important to understand the historical context that led to the creation of the first higher education courses in Brazil, the late institutionalization of the first university and the higher education s development in the country along the 20th century. The bibliographical revision about that period was important to understand the IES types that were created and the great expansion of the private sector, for the detriment of the public sector. The brief historical survey about evaluation showed the changes this practice had suffered until it started being used as a justification for public policies implanted to improve education s quality. To analyze the evaluation processes, we also made interviews with professionals who have participated for several years in internal and external evaluation processes in IES. The development of the first evaluation instruments, such as PARU, CNRES, GERES and PAIUB, occurred at the time when structural reforms were introduced in Brazil, aligning the country to the international agencies proposals, adopting the concept of Evaluator State. Critics have been made to the process of the reforms consolidation, which gave privileges to the private sector, boosting its great expansion. FHC s administration created ENC, known as Provão, whose results were used by media to make rankings with institutions and courses. With Lula as president, some intellectuals who were part of his government tried to do some changes and created SINAES, whose initial objective was to evaluate IES as a whole, considering ten dimensions. It was not difficult to notice this instrument suffered transformations and it retook the practice of ranking courses and institutions. We concluded that the evaluation promoted some improvement in IES and courses, especially due to the concern about being well placed in rankings. In spite of all the contradictions, we understand that the evaluation processes are necessary because of precarious conditions of many IES and courses that do not reach the minimum pattern of quality defined by MEC.